2018
DOI: 10.1038/s41598-018-29706-x
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene –dependent and –independent superficial scald resistance mechanisms in ‘Granny Smith’ apple fruit

Abstract: Superficial scald is a major physiological disorder of apple fruit (Malus domestica Borkh.) characterized by skin browning following cold storage; however, knowledge regarding the downstream processes that modulate scald phenomenon is unclear. To gain insight into the mechanisms underlying scald resistance, ‘Granny Smith’ apples after harvest were treated with diphenylamine (DPA) or 1-methylcyclopropene (1-MCP), then cold stored (0 °C for 3 months) and subsequently were ripened at room temperature (20 °C for 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 78 publications
2
48
0
2
Order By: Relevance
“…UDP-xylose is produced via catalysis by UDP-glucuronate decarboxylase [61]. The formation of xylans is accompanied by cross-linkages with lignin via alpha-L-arabinofuranosyl residues [62]. Methyltransferase involved in the formation of 4-O-methylglucuronoxylan in pea epicotyl is stimulated by UDP-D-xylose and UDP-D-glucuronic acid [63].…”
Section: Occurrence Of D-and L-carbohydrates Their Metabolism In Plamentioning
confidence: 99%
“…UDP-xylose is produced via catalysis by UDP-glucuronate decarboxylase [61]. The formation of xylans is accompanied by cross-linkages with lignin via alpha-L-arabinofuranosyl residues [62]. Methyltransferase involved in the formation of 4-O-methylglucuronoxylan in pea epicotyl is stimulated by UDP-D-xylose and UDP-D-glucuronic acid [63].…”
Section: Occurrence Of D-and L-carbohydrates Their Metabolism In Plamentioning
confidence: 99%
“…Symptoms of superficial scald are consistent among most susceptible varieties of pome fruit, and shown as brown-dark patches on the fruit skin, resulting from the necrosis of the epidermis and hypodermal cortical tissues 1,3 . While the molecular and physiological mechanisms underlying scald in apples have been largely studied over the past few years 2,3,[6][7][8] , scarce information is available regarding this disorder in pears. The most accepted theory for scald development focuses on the auto-oxidation of the acylic sesquiterpene α-farnesene into conjugate trienols (CTols), which leads to the production and release of the ketone 6methyl-5-hepten-2-one 4,[9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…An ethylene-independent regulation of scald has also been acknowledged, since treatment with diphenylamine (DPA) 7 or storage under very low oxygen-modified atmospheres 5 generally controls scald development in pome fruit, without inhibiting the fruit ethylene production capacity. Earlier studies 17 also showed that treatment of apples and pears with lovastatin, an inhibitor of the 3hydroxy-3-methylglutaryl-coenzyme A reductase (HMG-CoA reductase), responsible for the conversion of HMG-CoA to mevalonate, controlled scald without altering the fruit-ripening physiology.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, scald has been associated with high γ-aminobutyric acid (GABA) levels in 'Honeycrisp' apples [62]. More recently, Karagiannis et al [48] observed an extensive down-accumulation of several proteins following DPA treatment, verifying the importance of protein repression studies to scald prevention, namely cell membrane protection. Their closed global protein analysis showed that sulfur amino acids are possibly involved in scald [48].…”
Section: Effect Of Dpa On Amino Acidsmentioning
confidence: 99%
“…DPA also influenced the accumulation of total amino acids, in DPA treated-apples [61]. Postharvest literature in this field demonstrated that, when symptoms of superficial scald were high, the level of alanine, valine, leucine, serine, aspartic acid, methionine, cysteine, and phenylalanine in the fruit were also high, but lower in DPA-treated apples [48]. Moreover, scald has been associated with high γ-aminobutyric acid (GABA) levels in 'Honeycrisp' apples [62].…”
Section: Effect Of Dpa On Amino Acidsmentioning
confidence: 99%